Multi-omics analysis identifies IgG2b class-switching with ALCAM-CD6 co-stimulation in joint-draining lymph nodes during advanced inflammatory-erosive arthritis - Kenney, H. Mark; Rangel-Moreno, Javier; Peng, Yue; Chen, Kiana L.; Bruno, Jennifer; Embong, Abdul; Pritchett, Elizabeth; Fox, Jeffrey I.; Becerril-Villanueva, Enrique; Gamboa-Domínguez, Armando; Quataert, Sally; Muthukrishnan, Gowrishankar; et al. (Frontiers in Immunology, 2023)
Introduction Defective lymphatic drainage and translocation of B-cells in inflamed (Bin) joint-draining lymph node sinuses are pathogenic phenomena in patients with severe rheumatoid arthritis (RA). However, the molecular mechanisms underlying this lymphatic dysfunction remain poorly understood. Herein, we utilized multi-omic spatial and single-cell transcriptomics to evaluate altered cellular composition (including lymphatic endothelial cells, macrophages, B-cells, and T-cells) in the joint-draining lymph node sinuses and their associated phenotypic changes and cell-cell interactions during RA development using the tumor necrosis factor transgenic (TNF-Tg) mouse model. Methods Popliteal lymph nodes (PLNs) from wild-type (n=10) and TNF-Tg male mice with “Early” (5 to 6-months of age; n=6) and “Advanced” (>8-months of age; n=12) arthritis were harvested and processed for spatial transcriptomics. Single-cell RNA sequencing (scRNAseq) was performed in PLNs from the TNF-Tg cohorts (n=6 PLNs pooled/cohort). PLN histopathology and ELISPOT along with ankle histology and micro-CT were evaluated. Histopathology of human lymph nodes and synovia was performed for clinical correlation. Results Advanced PLN sinuses exhibited an increased Ighg2b/Ighm expression ratio (Early 0.5 ± 0.1 vs Advanced 1.4 ± 0.5 counts/counts; p<0.001) that significantly correlated with reduced talus bone volumes in the afferent ankle (R2 = 0.54, p<0.001). Integration of single-cell and spatial transcriptomics revealed the increased IgG2b+ plasma cells localized in MARCO+ peri-follicular medullary sinuses. A concomitant decreased Fth1 expression (Early 2.5 ± 0.74 vs Advanced 1.0 ± 0.50 counts, p<0.001) within Advanced PLN sinuses was associated with accumulation of iron-laden Prussian blue positive macrophages in lymph nodes and synovium of Advanced TNF-Tg mice, and further validated in RA clinical samples. T-cells were increased 8-fold in Advanced PLNs, and bioinformatic pathway assessment identified the interaction between ALCAM+ macrophages and CD6+ T-cells as a plausible co-stimulatory mechanism to promote IgG2b class-switching. Discussion Collectively, these data support a model of flare in chronic TNF-induced arthritis in which loss of lymphatic flow through affected joint-draining lymph nodes facilitates the interaction between effluxing macrophages and T-cells via ALCAM-CD6 co-stimulation, initiating IgG2b class-switching and plasma cell differentiation of the expanded Bin population. Future work is warranted to investigate immunoglobulin clonality and potential autoimmune consequences, as well as the efficacy of anti-CD6 therapy to prevent these pathogenic events.